A New Poverty Measure Aims for Consensus. Issue 6 (28th November 2018) - Purdam, Kingsley; Garratt, Elisabeth; Whitham, Graham
Abstract: The Social Metrics Commission wants all parties to agree on its approach to measuring poverty. Kingsley Purdam, Elisabeth Garratt and Graham Whitham assess its chances of success